Improving asbestos knowledge among demolition workers through training after earthquakes - Tuncer, Kevser; Gomleksiz, Mehtap (Sage Publications Inc, 2025)
Background Asbestos was widely used as insulation material in T & uuml;rkiye's construction. It poses severe health risks, including mesothelioma, a type of lung cancer that is often fatal.Objective This study aimed to determine and improve the knowledge about asbestos among employees of a building demolition workers in Elaz & imath;& gbreve;.Methods Out of 82 employees in the demolition workers, 75 volunteered for the study after ethical approval was obtained. Training materials and survey forms were developed through a review of the literature. Surveys were conducted before and after the training sessions. Data were analyzed using SPSS 22.0, and a p-value of less than 0.05 indicated statistical significance.Results The participants were exclusively male, with an average age of 39.06 years. Among them, 40% were current smokers. Most had not received prior training on asbestos. Before the training, nearly half of the respondents (49.4%) were unaware of the procedures for asbestos check and removal prior to demolition. knowledge across all surveyed areas. The knowledge of demolition workers increased significantly after training.Conclusion Training significantly improved asbestos-related knowledge which was low before among the demolition workers, a group at high risk for asbestos exposure.
Keywords: asbestos; knowledge; training; work; earthquake; demolition worker